Environmental Management of Larg Supply Chain: A Diagnostic Instrument Proposed for Assessing Suppliers - Josiano Cesar de Sousa; Murilo Barros Barros Alves; Leonardo Leocádio; Jaqueline Rossato (BBR: Brazilian Business Review)
This article addresses Supply Chain Management (SCM), focusing specifically on environmental management systems. A systematic review of the literature identified gaps in SCM studies and supported the development of a diagnostic tool model capable of measuring the level of involvement of suppliers in a Supply Chain (CS) with the Environmental Management program of a focal firm. The results of this study were synthesized in a diagnostic tool on which elaboration was based on the LARG SCM model, the Dynamic Capabilities model, and the Learning to Grow Methodology. The proposed model was structured to measure, through a graph, the level of involvement of the suppliers of an SC with the environmental management requirements based on ISO 14001: 2015. The model was tested on the supply chain of a company that was included in the ISE (2017) Corporate Sustainability Index and was validated by the surveyed company.